Piszczaleczka : piosenki i wierszyki ludowe - Wawilow, Danuta; Usenko, Oleg. (Warszawa : Krajowa Agencja Wydawnicza, 1990)
A selection of folk verse from around Poland for young children. Ages 5-8.
Keywords: Folk songs, Polish; Folk poetry, Polish; Children's poetry, Polish